1995
DOI: 10.1111/j.1600-0536.1995.tb00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact allergy to kojic acid in skin care products

Abstract: Kojic acid (5-hydroxy-2-(hydroxymethyl)-4-pyrone), a fungal metabolic product, has increasingly been used as a skin-depigmenting agent in skin care products marketed in Japan since 1988. In order to determine its frequency of sensitization, during 1 year from October 1992 to September 1993, we performed patch testing with it in 220 female patients with suspected cosmetic-related contact dermatitis. Of the 220 patients, 8 used at least 1 skin care product containing kojic acid, 5 of whom reacted to kojic acid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
109
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(114 citation statements)
references
References 12 publications
0
109
0
2
Order By: Relevance
“…Data are mean ± standard deviation. ## p < 0.01 compared with the vehicle-treated group, **p < 0.01 compared with the SCF-treated group (n = 3) possibility of kojic acid [9,10] and weak photostability of arbutin [25]. In this study, GAE showed good antimelanogenic activity similar to those of chemicals, and no adverse skin reactions including erythema, burning, or pruritus.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Data are mean ± standard deviation. ## p < 0.01 compared with the vehicle-treated group, **p < 0.01 compared with the SCF-treated group (n = 3) possibility of kojic acid [9,10] and weak photostability of arbutin [25]. In this study, GAE showed good antimelanogenic activity similar to those of chemicals, and no adverse skin reactions including erythema, burning, or pruritus.…”
Section: Discussionmentioning
confidence: 59%
“…However, these compounds have undesirable side effects and can be weakly active [9][10][11]. Thus, it is important to develop new depigmenting agents as inhibitors of melanin formation that are derive from natural sources, which will lessen the likelihood of unrelated cytotoxicity or other side effects [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is effective as a hypopigmenting agent [112], especially in combination with other substances, it has a high sensitizing potential and can cause contact dermatitis [113]. Concerns have been raised about a possible carcinogenic effect since kojic acid was associated with hepatic tumors when fed to p53 deficient mice [114].…”
Section: Chemical Effectorsmentioning
confidence: 99%
“…Although kojic acid had been widely used in skin care products in Japan, more recent clinical studies conducted there have demonstrated its highly sensitizing potential [22]. Kojic acid has also been recently banned from the Japanese market over mutagenicity concerns.…”
Section: Kojic Acidmentioning
confidence: 99%